Police Role In The Handling Of Hate Speech - Zaldy Kurniawan (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2018)
Development and advancement of technology in Indonesia is a form of improving the quality and quantity of human resources. Along with it, the technological advances giving positive and negative impacts on the nation Indonesia. As one of the negative impacts are increasingly banyakannya cyber crimes occurred. Of hate speech as one example of crime that can break the unity of the nation. Thus takes the role of the Police in order to make prevention and law enforcement against the emergence of hate speech in cyberspace. The current legal regulations still need to be updated to support the performance of the police. The role of the Government to promote prevention efforts are also expected to prevent the speech of hatred in the society.Keywords: Role of Police, Handling, Hate Speech.